PENGARUH KUALITAS PELAYANAN DAN PENGELOLAAN USAHA TERHADAP PARTISIPASI ANGGOTA KOPERASI JASA SIMPAN PINJAM (Studi Kasus Pada Koperasi Wanita Sekar Kartini Jember) - Sholekhah, Irmadatus; Rachmawati, Sela; Trisnanda, Aprilina; Choir, Nafisah Ummul; Ahmad, Surya Maulana (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The participation of cooperative members is essential to achieving cooperative business success. This is due to the member's position as owner and customer of the cooperative. This research aims to analyze the influence of service quality and business management on the participation of savings and loan service cooperative members. This research uses quantitative methods with a multiple linear regression analysis approach with the SPSS 25.0 application. The research respondents were 30 employees of the Sekar Kartini Women's Cooperative. The results of hypothesis testing (H1) show the Sig value for the influence of service quality on Y is 0.015 > 0.05, so it can be concluded that there is a partial influence of the service quality variable on the cooperative member participation variable. Meanwhile, the results of further hypothesis testing (H2) show the sig value for the influence of business management on Y is 0.016 < 0.05, so it can be concluded that there is a partial influence of the business management variable on the participation variable Cooperative Member. The significance value for the influence and management of X1 means that there is an influence of service quality and business management on cooperative member participation. Based on the results of this research, it is known that the R square value is 0.337; this means that the influence of variables X1 and X2 simultaneously on variable Y is 33.7%. This shows that improving service and management can help increase member participation in savings and loan services at the Sekar Kartini Women's Cooperative. Keywords: Business Management, Cooperative Member Participation, Service Quality.